ANALYZE THE INCOME AND WALFARE FISHERMAN SOCIETY AT PINANG SEBATANG TIMUR VILLAGE TUALANG DISTRICT SIAK REGENCY RIAU PROVINCE - Novalina, Sri Rapika; Nogroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted at Pinang Sebatang Timur Village Riau on September 2015. This research aimed to analyze the income and the distribution outcome fisherman household and to describe walfare fisherman society. The method use was survey method. The respondents were 17 fisherman and data was callected as primary and secondary data.The research results showed that the income of fisherman household who use the paddle canoe around about Rp 2.047.500-2.397.500, with the income average Rp 2.178.475/month and income of sideline fisherman household who use the paddle canoe around about Rp 2.026.500-2.526.000, with the income average Rp 2.201.357/month. The outcome of fisherman household who used the paddle canoe about Rp Rp.1.633.000-2.004.000 with the outcome average Rp 1.849.300/month and outcome of sideline fisherman household who used the paddle canoe about Rp 1.699.000-2.299.000 with the outcome average Rp 1.900.700/month.According to Siak Regency UMR, all of fisherman and sideline fisherman are above Siak Regency UMR, according to Bappenas, all of fisherman and sideline fisherman are prosperous, and according to BKKBN there are five household in the 1st prosperous family, 4 household in the 2nd prosperous family, and finally eight household in the 3th prosperous family.Keywords : Income, Outcome, Walfare, Fisherman and sideline fisherman Society